DESAIN PEMBELAJARAN MODEL KEMP DAN IMPLEMENTASINYA DENGAN TEKNIK JIGSAW - Mayangsari Nikmatur Rahmi; Imam Walid Asrofuddin Ulil Huda (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
Various kinds of events with the development of the times in the world of education today that have an impact on the quality of education. First, there are many teachers who find it difficult and complain in designing or designing learning using learning media so that the wrong target occurs. Second, the negative mindset of the teacher that teaching is troublesome, tiring, and difficult. Third, various kinds of student characters that can cause confusion for teachers, where to start educating them. Fourth, the tight competition in the world of education is the impact of globalization and MEA so that it demands quality education and is judged by the output of its graduates. The author provides answers to the problems presented, namely the application of the Kemp model of learning design with details of setting learning objectives, analyzing student characteristics, identifying materials, determining learning, determining pre-tests, determining teaching and learning activities, coordinating supporting facilities, and evaluating to facilitate teachers in designing effective, efficient and quality learning.